Therapies with Emerging Evidence of Efficacy: Avotermin for the Improvement of Scarring. (20th July 2010) - Bush, Jim; So, Karen; Mason, Tracey; Occleston, Nick L.; O'Kane, Sharon; Ferguson, Mark W. J.
Abstract : Many patients are dissatisfied with scars on both visible and non-visible body sites and would value any opportunity to improve or minimise scarring following surgery. Approximately 44 million procedures in the US and 42 million procedures in the EU per annum could benefit from scar reduction therapy. A wide range of non-invasive and invasive techniques have been used in an attempt to improve scarring although robust, prospective clinical trials to support the efficacy of these therapies are lacking. Differences in wound healing and scar outcome between early fetal and adult wounds led to interest in the role of the TGFβ family of cytokines in scar formation and the identification of TGFβ 3 (avotermin) as a potential therapeutic agent for the improvement of scar appearance. Extensive pre-clinical and human Phase I and II clinical trial programmes have confirmed the scar improving efficacy of avotermin which produces macroscopic and histological improvements in scar architecture, with improved restitution of the epidermis and an organisation of dermal extracellular matrix that more closely resembles normal skin. Avotermin is safe and well tolerated and is currently in Phase III of clinical development, with the first study, in patients undergoing scar revision surgery, fully recruited.